1964
DOI: 10.1152/ajplegacy.1964.206.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone of free fatty acid metabolism

Abstract: Bovine growth hormone ( GH) was administered at 1 mg/kg day for various periods of time to normal dogs. The effects produced on plasma free fatty acid ( FFA) metabolism were studied in these animals, in the unanesthetized state, using palmitate-C14. At 3–9 hr following intravenous injection of growth hormone significant increase were observed in plasma FFA concentration, turnover rate, total amount of FFA oxidized to CO2, and per cent of total respiratory CO2 derived from FFA. FFA production was increased by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

1965
1965
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Bodel, Rubenstein, McGarry, and Beck failed to show enhanced oxidation of palmitic acid-i-C14 by excised rat diaphragm either by addition of growth hormone in vitro or by pretreatment of the animals with growth hormone (25). On the other hand, de Bodo and colleagues (26,27), on the basis of studies in which C14 palmitate was infused into normal dogs, reported that growth hormone administration increased the turnover rate of FFA, the amount of FFA oxidized to CO2, and the fraction of total respiratory CO2 derived from FFA oxidation.…”
Section: Discussionmentioning
confidence: 95%
“…Bodel, Rubenstein, McGarry, and Beck failed to show enhanced oxidation of palmitic acid-i-C14 by excised rat diaphragm either by addition of growth hormone in vitro or by pretreatment of the animals with growth hormone (25). On the other hand, de Bodo and colleagues (26,27), on the basis of studies in which C14 palmitate was infused into normal dogs, reported that growth hormone administration increased the turnover rate of FFA, the amount of FFA oxidized to CO2, and the fraction of total respiratory CO2 derived from FFA oxidation.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, the fasting FFA levels in the four infants ill with marasmus were greater than the mean of the group, being 738, 920, 1000, and 1409 moles/liter. High levels of FFA are associated with increased FFA flux [13], which may also be due to the high GH [31] and low insulin levels in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of irreversible losses of glucose, acetate and palmitate were made by continuous intravenous infusion of the appropriate metabolite via one jugular catheter and subsequent collection of blood samples from the contralateral catheter. Palmitic acid was bound to plasma proteins (using fresh plasma from individual animals) as described by Winkler et al (1964). Infusion rates for each labelled metabolite were recorded.…”
Section: Metabolite Biokineticsmentioning
confidence: 99%
“…Specific radioactivities of respective metabolites were measured according to the procedures outlined by Jones (1965) for glucose; Pethick et al (1981) for acetate; Winkler et al (1964) for NEFA. Thus glucose was isolated as glucose penta-acetate, acetate was isolated as the volatile acid and total NEFA were separated from other labelled metabolites.…”
Section: Metabolite Biokineticsmentioning
confidence: 99%